Hydrothermally prepared Ag2MoO4 nanoparticles anchored on nitrogen doped rGO for asymmetric supercapacitor application - R. Shejini; V. Sabarinathan; K. Sethuraman; K. Mohanraj; J. Henry; G. Sivakumar (Chemical Physics Impact)
The energy density and the specific capacitance are two important parameters for improving energy storage devices. In this study, we introduce the novel incorporation of nitrogen-doped reduced graphene oxide (NRGO) into Ag2MoO4 nanoparticles, for use in asymmetric supercapacitor applications. The synthesized compounds were confirmed and characterized using structural, functional, nitrogen adsorption-desorption, surface, elemental analyses, and electrochemical properties. Here, the AMONRGO composite materials exhibited the pebble stone-like structure of Ag2MoO4 on the NRGO surface, observed by FESEM techniques. At 1 Ag-1, the Ni foam coated with the AMONRGO (II) nanocomposite demonstrates a good Csp of 648 Fg-1. It displayed retention of 91 % of its initial capacitance over 5000 charge/discharge cycles. In an asymmetric supercapacitor (ASC) device, the electrodes of AMONRGO (II) || AC demonstrated an exceptional energy density (Ed) of 44.13 Whkg-1 at a discharge rate (597.79 Wkg-1). The results suggest that the AMONRGO electrodes exhibit promising electrochemical performance for the supercapacitor application.